CRESCIMENTO DE MUDAS DE ACHACHAIRU (GARCINIA HUMILIS) EM DIFERENTES NIVEIS DE SOMBREAMENTO - SILVA, Bruna Luzia Barbosa; COSTA, Edilson; PAULA, Fernando Oliveira; SALLES, Josiane Souza1; FERREIRA, Thales silva; LIMA, Alexandre Henrique Freitas (ANAIS DO ENIC, 2017)
-